New Zealand Ceratocumatidae and Nannastacidae (Crustacea: Cumacea) - Gerken, Sarah (Zootaxa, 2012)
The cumacean fauna of New Zealand has been little studied, and recent collecting on the Chatham Rise and ChallengerPlateau has yielded many new species and new genera. The first record of the family Ceratocumatidae is reported fromNew Zealand waters, Cimmerius sp. Within the Nannastacidae, there are only two previously described nannastacidspecies from New Zealand, Campylaspis rex Gerken & Ryder 2002 and Scherocumella pilgrimi (Jones 1963). The recentcollections yielded one new nannastacid genus, Aotearocumella n. gen., and 22 new nannastacid species, Aotearocumellaacantha n. sp. A. echinoseta n. sp., A. watlingi n. sp., Atlantocuma confunda n. sp., Campylaspenis tangaroae n. sp.,Campylaspis apheles n. sp., C.bituberculata n. sp., C. hatchae n. sp., C. macrosulcata n. sp., C. microsulcata n. sp., C.millsae n. sp., C. normani n. sp., C. rufus n. sp., C. schnabelae n. sp., C. sculptaspinosa n. sp., C. zealandiaensis n. sp., C.zimmeri n. sp., Procampylaspis chathamensis n. sp., P. rhypakoceros n. sp., P. rhypakos n. sp., Schizocuma delicata n. sp., and Styloptocuma gordoni n. sp. In addition, a neotype for C. rex is designated.